CATALYZING ORGANIZATIONAL EXCELLENCE: ANALYZING THEPROFOUND INFLUENCE OF DIGITAL LEADERSHIP ON HUMAN RESOURCE PERFORMANCE IN CONTEMPORARY CORPORATE ENVIRONMENTS - Wafi Ali Hajjaj; Diana Hayati; Sabirin; Zainal Arifin; Benius (CV. Adiba Aisha Amira, 2024)
In the dynamic landscape of the modern business world, the emergence of the digital era has ushered in transformative changes. Traditional leadership paradigms have given way to digital leadership, focused on technology, data- driven decision-making, innovation, and open organizational cultures. This study delves into the intricate relationship between digital leadership and human resource (HR) performance within contemporary corporate environments. It aims to explore how adopting digital leadership practices influences HR performance metrics and contributes to organizational excellence. Through a mixed-method approach, combining quantitative and qualitative analyses, the research uncovers significant positive correlations between digital leadership practices and HR performance. Key findings reveal that technology adoption, data-driven decision- making, innovation, and open cultures drive enhanced HR performance. This study offers critical insights into how organizations can navigate the complexities of the digital age by strategically adopting digital leadership practices. By fostering a culture of technology adoption, data-driven decision-making, innovation, and open communication, organizations can position themselves for success in the digital era.